Meeting the Personnel Needs of Anambra State Industrialists in Nigeria: A Call for Mathematics Education Reforms - Ebele C Okigbo; Amarachukwu N Nwoye (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2012)
The study examined that extent the mathematics education graduates meet the personnel needs of the industrialists in Anambra State. Ninety-four (94) out of 198 managers (employers) from the three private industrial zones in Anambra State, Nigeria were included in the investigation. A descriptive survey instrument was constructed by the researchers based on professional and ICT competencies which incorporated 25 items. Analysis of results showed that: a. Mathematics education graduates posses all the needed professional competencies as identified by Industrialists, b. 41.7% of the needed ICT competencies were acquired by the graduates while 58.3% were not, c. There is a significant difference in the mean ratings of the Industrialists on the expected versus acquired ICT competencies of mathematics education graduates. The findings of the study suggest that Nigeria's mathematics education program should be revised to reflect the acquisition of ICT skills within the mathematics contents.